Risk avoidance in sympatric large carnivores: reactive or predictive?. (20th May 2013) - Broekhuis, Femke; Cozzi, Gabriele; Valeix, Marion; McNutt, John W.; Macdonald, David W.; Fryxell, John
Summary Risks of predation or interference competition are major factors shaping the distribution of species. An animal's response to risk can either be reactive, to an immediate risk, or predictive, based on preceding risk or past experiences. The manner in which animals respond to risk is key in understanding avoidance, and hence coexistence, between interacting species. We investigated whether cheetahs (Acinonyx jubatus), known to be affected by predation and competition by lions (Panthera leo) and spotted hyaenas (Crocuta crocuta), respond reactively or predictively to the risks posed by these larger carnivores. We used simultaneous spatial data from Global Positioning System (GPS) radiocollars deployed on all known social groups of cheetahs, lions and spotted hyaenas within a 2700 km2 study area on the periphery of the Okavango Delta in northern Botswana. The response to risk of encountering lions and spotted hyaenas was explored on three levels: short‐term or immediate risk, calculated as the distance to the nearest (contemporaneous) lion or spotted hyaena, long‐term risk, calculated as the likelihood of encountering lions and spotted hyaenas based on their cumulative distributions over a 6‐month period and habitat‐associated risk, quantified by the habitat used by each of the three species. We showed that space and habitat use by cheetahs was similar to that of lions and, to a lesser extent, spotted hyaenas. However, cheetahs avoided immediate risks by positioning themselves further from lions and spotted hyaenas than predicted by a random distribution. Our results suggest that cheetah spatial distribution is a hierarchical process, first driven by resource acquisition and thereafter fine‐tuned by predator avoidance; thus suggesting a reactive, rather than a predictive, response to risk.